2018
DOI: 10.3389/fpls.2018.01005
|View full text |Cite
|
Sign up to set email alerts
|

ZmCom1 Is Required for Both Mitotic and Meiotic Recombination in Maize

Abstract: CtIP/Ctp1/Sae2/Com1, a highly conserved protein from yeast to higher eukaryotes, is required for DNA double-strand break repair through homologous recombination (HR). In this study, we identified and characterized the COM1 homolog in maize. The ZmCom1 gene is abundantly expressed in reproductive tissues at meiosis stages. In ZmCom1-deficient plants, meiotic chromosomes are constantly entangled as a formation of multivalents and accompanied with chromosome fragmentation at anaphase I. In addition, the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Com1/Sae2 was first identified in Saccharomyces cerevisiae (Prinz et al, 1997;McKee and Kleckner, 1997) with an indispensable role in meiosis. In subsequent years, Com1/Sae2 homologs have been identified in mammals (Schaeper et al, 1998), fission yeast (Limbo et al, 2007), Caenorhabditis elegans (Penkner et al, 2007), Arabidopsis (Uanschou et al, 2007), Tetrahymena (Lukaszewicz et al, 2010), Oryza sativa (Ji et al, 2012), and Zea mays (Wang et al, 2018). As the specific mechanisms in S. cerevisiae, Sae2 acts together with the MRX complex to initiate 5'-3' end resection by endonucleolytic cleavage, and the resulting 3' single-strand is subsequently used for Rad51 or Dmc1-catalyzed strand invasion to initiate homology-directed repair (Cannavo and Cejka, 2014;Garcia et al, 2011;Neale et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Com1/Sae2 was first identified in Saccharomyces cerevisiae (Prinz et al, 1997;McKee and Kleckner, 1997) with an indispensable role in meiosis. In subsequent years, Com1/Sae2 homologs have been identified in mammals (Schaeper et al, 1998), fission yeast (Limbo et al, 2007), Caenorhabditis elegans (Penkner et al, 2007), Arabidopsis (Uanschou et al, 2007), Tetrahymena (Lukaszewicz et al, 2010), Oryza sativa (Ji et al, 2012), and Zea mays (Wang et al, 2018). As the specific mechanisms in S. cerevisiae, Sae2 acts together with the MRX complex to initiate 5'-3' end resection by endonucleolytic cleavage, and the resulting 3' single-strand is subsequently used for Rad51 or Dmc1-catalyzed strand invasion to initiate homology-directed repair (Cannavo and Cejka, 2014;Garcia et al, 2011;Neale et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome fragmentation and entanglement are characteristic phenomena observed in mutants deficient in DSB repair machinery. Like the Osrad17 mutants (Hu et al, 2018) and other related mutants such as Zmcom1 (Wang et al, 2018), Zmrad51c (Jing et al, 2019), Osxrcc3 (Zhang et al, 2015), Atrad50 (Gallego et al, 2001;Bleuyard et al, 2004) and Atmre11 (Samanic et al, 2013(Samanic et al, , 2016, the Zmrad17 mutants showed the presence of chromosome fragmentation at prophase I. However, the severity of chromosome aberration seemed to be much less in Zmrad17 when compared to the Osrad17 mutants.…”
Section: Discussionmentioning
confidence: 86%
“…HR is initiated by the programmed formation of DNA double-strand breaks (DSBs), which are catalyzed by a topoisomerase-like protein SPO11 and several accessory proteins (Keeney et al, 1997;Lam and Keeney, 2015). DSB sites are further resected by a protein complex known as MRX/N (Mre11-Rad50-Xrs2/Nbs1) and Sae2/Com1/CtIP/Ctp1 (Lamarche et al, 2010;Wang et al, 2018), generating replication protein A (RPA)-coated single-stranded DNA (ssDNA) overhangs (Mimitou and Symington, 2009). Then, RPA is replaced by the RecA recombinases RAD51 and DMC1 forming nucleoprotein filaments and promoting homology search and single strand invasion to produce recombination intermediates called as the displacement (D)-loop Cloud et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate whether defective ZmMTOPVIB disrupts homologous chromosome pairing, we performed fluorescence in situ hybridization (FISH) using the 5S rDNA probe in wild type and the ZmmtopVIB-1 mutant. The 5S rDNA is a tandem repeat sequence located on the long arm of chromosome 2 that is routinely used to evaluate chromosome pairing and segregation in maize (Wang et al, 2018). In wild type meiocytes, two 5S signals gradually pair with each other during zygotene ( Figure The telomere bouquet is an evolutionarily conserved chromosome arrangement that clusters telomeres in a small region on the nuclear envelope (Tomita and Cooper, 2007;Moiseeva et al, 2017).…”
Section: Zmmtopvib Is Critical For Homologous Pairing But Not Requirementioning
confidence: 99%